To the problem of brain surgery complications (review) - P. G. Shnyakin; I. E. Milekhina; I. A. Kazadaeva (Сибирский научный медицинский журнал, 2021)
The development of complications as a result of neurosurgical operations is an urgent problem nowadays. Various approaches to the classification of complications are presented in the literature. They are based on the nature of the complications, the time of development, the duration of the neurological deficit, the direct connection of the complications with the surgical intervention, methods of their treatment, etc. On the average, the complication rate ranges from 5 to 28 %. In brain operations, the risk of complications is higher than in spinal surgery. The reasons for their development are various and are associated with surgical intervention, the course of the postoperative period, the somatic status of the patient before surgery and the initial pathology that required surgical treatment. From 7 to 24 % of patients require readmission within 30 days after discharge from the hospital due to complications. There are infectious, thromboembolic complications and the appearance or growth of a neurological deficit. The development of complications is associated with a deterioration in the quality of treatment, an increased risk of patient disability and death.